Better Disease Control by Multidrug Regimen in Scabies: A Randomized Controlled Trial - Prajwal Pandey; Sudha Agrawal (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Scabies is a highly resilient condition with varying morbidity worldwide. The treatment options widely used for the disease include topical permethrin 5% and oral Ivermectin with similar efficacy. Treatment failure due to non-compliance is a major problem with the current treatment modalities.